2013
DOI: 10.1007/978-3-7091-1434-6_24
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Hematoma of the Posterior Fossa

Abstract: Posterior fossa injury is rare, occurring in less than 3 % of head injuries. We retrospectively reviewed patients' clinical and radiological findings, management, and outcomes. The aim of the present study was to investigate the features of posterior fossa hematoma, including posterior fossa epidural hematoma (EDH), posterior fossa subdural hematoma (SDH), and intracerebellar hematoma. From January 1995 to January 2009, 4,315 patients with head trauma were hospitalized at our institution. The -present study fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…It accounts for less than 0.13% to 1.9% of all traumatic head injuries. [ 2 3 ] The rarity is because of the early ossification and due thickness of the basioccipital bone, resulting in less amount of fracture as compared to supratentorial counterparts. PFEDH accounts for 4%–12.9% of all acute extradural hematoma cases.…”
Section: Ncidencementioning
confidence: 99%
“…It accounts for less than 0.13% to 1.9% of all traumatic head injuries. [ 2 3 ] The rarity is because of the early ossification and due thickness of the basioccipital bone, resulting in less amount of fracture as compared to supratentorial counterparts. PFEDH accounts for 4%–12.9% of all acute extradural hematoma cases.…”
Section: Ncidencementioning
confidence: 99%
“…Compared with the aforementioned traumatic brain injuries, traumatic posterior fossa mass lesions are rare. In a recent retrospective review of 4315 patients of hospitalized TBI patients, only 41 (1%) were noted to have posterior fossa hematomas [50]. In these 41 patients, there were 18 patients with posterior fossa EDH, 10 with SDH, and 17 with intracerebellar hematoma [50].…”
Section: Traumatic Posterior Fossa Mass Lesionsmentioning
confidence: 99%
“…In a recent retrospective review of 4315 patients of hospitalized TBI patients, only 41 (1%) were noted to have posterior fossa hematomas [50]. In these 41 patients, there were 18 patients with posterior fossa EDH, 10 with SDH, and 17 with intracerebellar hematoma [50]. EDH is the most common posterior fossa lesion reguiring surgery, followed by SDH and intracerebellar hemorrhage [7].…”
Section: Traumatic Posterior Fossa Mass Lesionsmentioning
confidence: 99%
“…supratentorial subdural hematomas (SDHs) are one of the commonest diseases encountered in the neurosurgical practice. Takeuchi and colleagues [8] analyzed 4315 patients with head trauma from 1995 to 2005. They found that 41(1%) their patients had traumatic hematomas of the posterior fossa and of those, only 10 had SDHs.…”
Section: Intracranialmentioning
confidence: 99%